Explaining voter turnout inequality in post-communist Eastern Europe: income inequality, institutions, and the normalization of voting - Northmore-Ball, K (2014)
This research examines the causes of turnout inequality in post-Communist Eastern Europe, particularly focusing on how macro-level contextual factors influence voter turnout across socioeconomic groups (by education, income, occupation class). I use repeated cross-sectional survey data covering twelve countries from the collapse of communism in 1989 to the late 2000s. I show that unlike in established democracies, turnout inequality cannot be simply explained by how easy it is to vote as determined by various institutions, such as voter registration rules and ballot complexity, and neither can turnout inequality be explained by disengagement among the losers in the economic transition. Instead turnout inequality is primarily determined by the interaction between the level political motivation of individual voters, which is the product of early life political socialization, and factors related to the transition process itself, such as the waning of the initial excitement with democratic elections. Income inequality appears to indirectly discourage educated and discerning voters by reinforcing the conditions, such as the dominance of clientelistic and paternalistic parties and corruption, which render electoral choices less meaningful.